AMPK-PINK1/Parkin Mediated Mitophagy Is Necessary for Alleviating Oxidative Stress-Induced Intestinal Epithelial Barrier Damage and Mitochondrial Energy Metabolism Dysfunction in IPEC-J2 - Shuting Cao; Hao Xiao; Xin Li; Jiang Zhu; Jingchun Gao; Li Wang; Caihong Hu (MDPI AG, 2021)
The imbalance of redox biology and oxidative stress leads to intestinal barrier injury and mitophagy. However, much uncertainty still exists about the role of mitophagy in oxidative stress and intestinal function. Here, we showed the effects of hydrogen peroxide (H2O2)-induced oxidative stress on intestinal epithelial cell oxidation balance, intestinal barrier function and mitochondrial energy metabolism and its underlying mechanism. In this study, we found that H2O2-induced oxidative stress activated adenosine monophosphate-activated protein kinase (AMPK) and enhanced mitophagy in intestinal porcine epithelial cells (IPEC-J2). While compound C (AMPK inhibitor) and mdivi-1 (mitophagy inhibitor) significantly reduced the activity of superoxide dismutase (SOD) and increased mitochondrial reactive oxygen species (ROS) levels in H2O2 treated cells. Moreover, compound C and mdivi-1 significantly reduced the trans-epithelium electrical resistant (TER) and increased the fluorescein isothiocyanate-dextran (FD4) flux in H2O2 treated IPEC-J2. Furthermore, compound C and mdivi-1 significantly reduced the activity of mitochondrial complex II. Seahorse XF96 data showed that compound C + mdivi-1+ H2O2 treatment significantly reduced maximum respiratory oxygen consumption and spare respiratory capacity. Additionally, compound C or mdivi-1 treatment reduced the formation of mitochondrial autophagosomes. These results unveiled that AMPK and PINK1/Parkin mediated mitophagy is necessary for alleviating oxidative stress induced intestinal epithelial barrier damage and mitochondrial energy metabolism dysfunction in IPEC-J2.